2001
DOI: 10.1097/00005392-200106001-00043
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Treatment of Urinary Incontinence: Long-Term Evaluation of the Results

Abstract: Injection of polydimethylsiloxane at the bladder neck achieved continence in 34% of neurogenic bladder cases. Results were better in girls with a stable bladder. Results deteriorated in the first 12 months of followup. No more than 3 injections are advised if a satisfactory result is not achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
5
6
0
Order By: Relevance
“…We confirm, like Guys et al [14], that Macroplastique causes no allergic reaction, and similar to previous reported series [14,16,17], submucosal injection with bulking agent is easy in children, with minimal morbidity and in an outpatient setting. As reported by others [18,19] we encountered no deterioration of the upper tracts due to any increase in the voiding pressure.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We confirm, like Guys et al [14], that Macroplastique causes no allergic reaction, and similar to previous reported series [14,16,17], submucosal injection with bulking agent is easy in children, with minimal morbidity and in an outpatient setting. As reported by others [18,19] we encountered no deterioration of the upper tracts due to any increase in the voiding pressure.…”
Section: Discussionsupporting
confidence: 93%
“…In the present series, a history of previous BNR did not improve the chances of a better outcome with Macroplastique injection; this is in agreement with Guys et al [14]. Although others have reported that the results are better in patients with Young-Dees BNR [16], patients with EEC fare better than those with neurogenic bladders [16,20,21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Positive aspects in favour of bulking agents are lower costs, shorter hospitalization, and less trauma in the patient than major continence surgical procedures [34]. Interestingly, Guys et al reported the results of a similar prospective study in 46 children with major structural incontinence related to neuropathic bladder dysfunction that was treated with endoscopic polydimethylsiloxane injections [35]. On the other hand, Dyer et al in their series of 34 patients who underwent primary injection of bulking agents did not find a significant improvement in continence, concluding that is often ineffective and expensive [36].…”
Section: Discussionmentioning
confidence: 99%
“…[2–6] Other methods like placement of artificial or autologous bulking agent have also been described creating a fixed bladder outlet resistance. [7] Recently, creation of innervation preserving composite outlet resistance similar to the mechanism provided by the nature comprising of smooth as well as striated muscle reconstruction as one unit has been described by us. [8]…”
Section: Introductionmentioning
confidence: 99%